2013
DOI: 10.1016/j.visres.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Object recognition in congruent and incongruent natural scenes: A life-span study

Abstract: Efficient processing of our complex visual environment is essential and many daily visual tasks rely on accurate and fast object recognition. It is therefore important to evaluate how object recognition performance evolves during the course of adulthood. Surprisingly, this ability has not yet been investigated in the aged population, although several neuroimaging studies have reported altered activity in high-level visual ventral regions when elderly subjects process natural stimuli. In the present study, colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 55 publications
3
47
1
1
Order By: Relevance
“…Although we feel that this encompassing definition is more true to the overall meaning of a scene (Zelinsky, 2013), we can draw parallels between our definition of typicality and other scene perception studies that have examined the role of either category typicality (Ehinger, Xiao, Torralba, & Oliva, 2011;Torralbo et al, 2013) or object typicality (Biederman, Mezzanotte, & Rabinowitz, 1982;Davenport & Potter, 2004;Joubert, Fize, Rousselet, & Fabre-Thorpe, 2008;Rémy et al, 2013;Võ & Henderson, 2009) on scene understanding. It has been shown that images that are more typical exemplars of a scene category are recognized better by both human observers (Torralbo et al, 2013) and computer vision classifiers (Ehinger et al, 2011), possibly because typical images have lower within-class variability (Torralbo et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Although we feel that this encompassing definition is more true to the overall meaning of a scene (Zelinsky, 2013), we can draw parallels between our definition of typicality and other scene perception studies that have examined the role of either category typicality (Ehinger, Xiao, Torralba, & Oliva, 2011;Torralbo et al, 2013) or object typicality (Biederman, Mezzanotte, & Rabinowitz, 1982;Davenport & Potter, 2004;Joubert, Fize, Rousselet, & Fabre-Thorpe, 2008;Rémy et al, 2013;Võ & Henderson, 2009) on scene understanding. It has been shown that images that are more typical exemplars of a scene category are recognized better by both human observers (Torralbo et al, 2013) and computer vision classifiers (Ehinger et al, 2011), possibly because typical images have lower within-class variability (Torralbo et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Regardless of age, objects and surrounding congruent scenes are processed and encoded together (Fenske, Aminoff, Gronau, & Bar, 2006; Rémy et al, 2013). Moreover, spatial contextual information perceptually primes subsequent object recognition, and face recognition is enhanced by reinstatement and impeded by deletion of encoding context (Memon & Bruce, 1983; Watkins, Ho, & Tulving, 1976; Winograd & Rivers-Bulkeley, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is the extent to which there is cognitive decline in this period that may be associated with steroid decline, and not only aging per se , and if there is a critical window for beneficial effects of hormone-replacement [123], [124], and [125]. Aging and neurodegeneration influence many cognitive abilities, including object recognition (see [126], [127], [128], and [129]).…”
Section: Effects Of Progestogens For Cognitive Performance Among Wmentioning
confidence: 99%